Lactation curve modelling using Legendre Polynomial in Sahiwal cattle - PRAKASH, VED; GUPTA, A K; GUPTA, ATUL; GANDHI, R S (The Indian Journal of Animal Sciences, 2016)
Present study aimed at modelling lactation curve in Sahiwal cattle using normalized Legendre polynomials functions of standardized units of time and understanding the variation of lactation curve in different lactations. Among the first three lactations, third lactation recorded highest peak yield as well other test day yields except the last test day yield. Further, first lactation curve was flatter compared to second and third lactation curve. Among the six different Legendre polynomial model considered higher degree Legendre polynomial model LEG5 and LEG6 fitted lactation curve better. Overall fifth degree Legendre polynomial lactation curve model (LEG5) can be used for accurate fitting for lactation curve in Sahiwal cattle as it gave almost similar accuracy like LEG6 with less parameter fitted.